Novel Predictive Nomogram for Identifying Difficult Guidewire Insertion in Patients With Malignant Colorectal Obstruction and Sphincterotome-Assisted Guidewire Insertion for Improving the Success Rate of Self-Expandable Metal Stent Insertion - Zhu, Zhenhua; Li, Biming; Liao, Wangdi; Lv, Nonghua; Chen, Youxiang; Shu, Xu (Frontiers in Oncology, 2020)
Aims: To identify risk factors associated with guidewire insertion (GWI) failure and construct a novel predictive nomogram. In addition, sphincterotome-assisted guidewire insertion (SAGWI) in difficult cases was evaluated for efficacy and safety. Methods: We retrospectively reviewed the data of 509 patients with malignant colorectal obstruction who underwent endoscopic SEMS insertion from 2007 to 2018 in our center. Multivariate logistic regression analysis was used to identify risk factors associated with GWI failure and construct a novel predictive nomogram. Improvements in the GWI, technical and clinical success rates were assessed for the SAGWI technique. Results: In a total of 509 patients with malignant colorectal obstruction, a 6.9% and 7.0% increase was found in the GWI success rate by intention-to-treat (ITT; p<0.001) and per-protocol (PP; p<0.001) analyses after SAGWI, respectively. A 6.5% and 6.6% increase in the technical success rate was found by ITT (p<0.001) and PP (p<0.001) analyses after SAGWI, respectively. A 5.8% and 6.0% increase in the clinical success rate was found by ITT (p<0.001) and PP (p<0.001) analyses after SAGWI, respectively. Regarding the GWI failure-related factors, a sharply angulated stricture was an independent risk factor, and an experienced colonoscopist was an independent protective factor. A novel effective predictive nomogram was constructed. Conclusion: The novel predictive nomogram can be conveniently used to identify difficult cases. A sharply angulated stricture and an experienced colonoscopist are independent factors related to GWI failure. The SAGWI technique is an effective and safe method for addressing technically difficult cases.